The Influence of Liquidity, Solvency, and Activity Ratios on Profitability (ROA) in Banking Companies Listed on the Indonesia Stock Exchange During 2021–2024 - Nugraha, Ari; Fauzan, Raihan; Komara, Acep (Dinasti Publisher, 2025)
This study aims to analyze the influence of liquidity, solvency, and activity ratios on profitability (Return on Assets/ROA) in banking companies listed on the Indonesia Stock Exchange during 2021–2024. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), the results reveal that the activity ratio (Total Asset Turnover/TATO) significantly and positively affects profitability. In contrast, the liquidity ratio (Loan to Deposit Ratio/LDR) and solvency ratio (Debt to Equity Ratio/DER) do not significantly influence profitability. These findings highlight that efficient asset management plays a crucial role in enhancing bank performance. Empirically, this implies that banking firms should prioritize asset utilization strategies to improve financial outcomes. From a managerial perspective, the results suggest the need for focused efforts on optimizing operational efficiency over merely maintaining liquidity or adjusting capital structure.